2016
DOI: 10.11138/mltj/2016.6.2.205
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of autologous leukocyte-reduced platelet-rich plasma therapy for patellar tendinopathy in a rat treadmill model

Abstract: SummaryBackground: An autologous platelet-rich plasma (PRP) therapy has currently been applied for the tendinopathy; however, its efficacy and an optimal platelets concentration in PRP were uncertain. We analyzed them in an animal model prepared using a repetitive running exercise. Methods: We made the tendinopathy rat model of patellar tendon using a rodent treadmill machine. Rats with tendinopathy were injected with leukocyte-reduced PRP at the platelets concentration of 1.0×10 6 /µL (P10 group), PRP at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…Recent reports have shown that the presence of leukocytes in PRP preparations may be detrimental to healing, due to their involvement in the inflammatory response [ 27 ] causing loss of pain relief efficacy [ 28 ]. We avoided this complication, because our PRP was prepared with nearly complete absence of leukocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports have shown that the presence of leukocytes in PRP preparations may be detrimental to healing, due to their involvement in the inflammatory response [ 27 ] causing loss of pain relief efficacy [ 28 ]. We avoided this complication, because our PRP was prepared with nearly complete absence of leukocytes.…”
Section: Discussionmentioning
confidence: 99%
“…To determine which dose of O-rPRP was more protective against toxic galactose, two doses of rPRP (0.25 and 0.5 ml/kg) [ 30 , 31 ] were tested. Upon administration, rPRP was diluted with PBS at 1:3 (0.25 and 0.5 ml/kg rPRP were added into 0.5 and 1 ml of PBS respectively) and mixed thoroughly.…”
Section: Methodsmentioning
confidence: 99%
“…However, other clinical studies found that PRP reduces or eliminates pain, such as that associated with tendinosis,911 rotator cuff tears,12,13 osteoarthritis,14 plantar fasciitis,15 and muscle injuries 16. PRP is also reported to act as an analgesic in animal pain models, such as rat tendinosis,17 rotator cuff injury,18 and dog tendon injury 19. In general, the findings of PRP analgesic influence led to the conclusion that although there are suggestions that PRP can act as an analgesic, the variability in study outcomes resulted from their small study sample sizes and the inclusion of too many variables, which did not allow the studies to be compared, or that the comparative analyses of the outcomes of different studies do not provide sufficient statistical support for the conclusion that PRP acts as an analgesic 4…”
Section: Introductionmentioning
confidence: 99%
“…One clinical study reported that PRP with a platelet concentration of 4- to 5-fold above average baseline count (varying from 1.5 and 3×10 5 /μL) enhanced peri-implant bone regeneration, while both lower and higher concentrations had inhibitory effects 59. A study on the rat tendinopathy model found that PRP with a platelet concentration of 1.0×10 6 / μ L induced complete pain relief, whereas PRP with half the platelet concentration induced significantly less pain relief 17. However, knowing what concentration of platelets in PRP induces the maximum analgesic effect requires understanding more than just the PRP platelet concentration.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation